ELECTRIC VEHICLE START FINGERPRINT IGNITION SYSTEM - Mrs. Megha; Nandini R.; Matin; Chaitra; Prabhuling (International Educational Journal of Science and Engineering, 2026)
From earlier times, security was and also till now is an issue of concern in our cars, vehicles and also in office, shops, etc. Everyone has a fear of unauthorized person entering to their home or office without their knowledge. The car ignition can be fitted with locks which are capable of breaking with the use of an alternate key. Alternatives to this system can be found like the password or pattern system in the locks which again has the possibility of getting exposed and opening the lock. So, a solution to such problems can be by combining car door lock with biometrics and IOT. Biometric verification is any means by which a person can be uniquely identified by evaluating one or more distinguishing biological traits. Unique identifiers include fingerprints, hand geometry, earlobe geometry, retina and iris patterns, voice waves, DNA, and signatures. Here we will use fingerprint for biometric verification as it is one such thing which is unique to every individual and the use of fingerprint as the key to ignition locks can overcome the security problem of unauthorized people trespassing to our homes, shops, offices, etc. to a great extent as delicacy in such key is not possible. Also, this system will not lead to problems like losing keys because we do not require carrying keys if this system is used instead of traditional locks. So, using Arduino and IOT we will try to implement the system with features which will increase the security level. This concept which is of Fingerprint car ignition lock is related to the security issues in the day today life, the physical key can be made as duplicate in very cheap cost and the key can lost somewhere or the key can steal, to overcome these issues we can use biometric security gadgets and try improvise the security much more because it can never be stolen it cannot be lost and the stealing chance of duplication are very low to break the security. From the old times the security is the big issue for the company’s houses and other places and every person is worried about the security now a days. The traditional ignition locks can be bypasses by the duplicate keys, but the best solution for this situation is biometric locks which include Fingerprints, Iris and Handprint scanners.so in this project we are going to try to get upper level of security.